Análisis y relación de la capacidad de intercambio catiónico con parámetros físicos y químicos en suelos de cinco sistemas productivos en Cotopaxi, mediante metodologías y aplicaciones móviles. - Changoluisa Caisaluisa, Nataly Rocio (2024)
Currently, soil health is important to ensure that farmers adopt new sustainable practices to ensure good food health. The present research was conducted in agreement with the Ekorural Foundation in the project "Agriculture for life" and was established at the Technical University of Cotopaxi, the same that aims to evaluate the cation exchange capacity (CIC) in soils of different production systems (agroecological, conventional, traditional, degraded and reference ecosystem) in three areas such as: Salache CEYPSA, Isinche and Carrillo with three methodologies to obtain (CIC) which are : staining with methylene blue (AM), soil calcination (MO), with saturated paste (pH), and two mobile technologies such as LandPKS to obtain the (color) and Slakes for (aggregate stability). With the methylene blue staining method, the maximum CIC was 4.8 meq/100g in the agroecological system located in Salache and a minimum of 0.83 meq/100g in a degraded system in the same area. The results obtained from the (AM) and (INIAP) analyses show similarity with a total CIC between 0-15 meq/100g, estimating these soils as poor. To verify the validity of the mobile applications, the results were compared under a Pearson correlation with an average linear relationship of 0.36 organic matter and 0.19 pH, while aggregate stability -0.31 and color -0.12 indicate that there is still a relationship with a weak correlation which will not influence the CIC. These methodologies and applications will contribute to the producers in knowing in a simple and low cost way the health of the soil.